2022
DOI: 10.3390/vaccines10050716
|View full text |Cite
|
Sign up to set email alerts
|

New Onset of Eosinophilic Granulomatosis with Polyangiitis Following mRNA-Based COVID-19 Vaccine

Abstract: Anti-SARS-CoV-2 vaccines are safe and effective, also in individuals with allergic and immune-mediated diseases (IMDs). There are reports suggesting that vaccines may be able to trigger de-novo or exacerbate pre-existing IMDs in predisposed individuals. Eosinophilic granulomatosis with polyangiitis (EGPA) is a small-vessel vasculitis characterized by asthma, eosinophilia, and eosinophil-rich granulomatous inflammation in various tissues. We describe the case of a 63-year-old man who experienced cardiac, pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…mRNA-based vaccines promote secretion of type I interferons and that increased interferon-I production is associated with asthma exacerbation [15,16]. Nappi et al reported a case in which two doses of the adenovirus-vectored vaccine ChAdOx1 (Astra Zeneca) progressively worsened asthma and a subsequent dose of the COVID-19 vaccine mRNA-1273 (Moderna) triggered eosinophilic granulomatosis with polyangiitis [17]. Regardless of the type of vaccine, COVID-19 vaccination itself may exacerbate asthma.…”
Section: Discussionmentioning
confidence: 99%
“…mRNA-based vaccines promote secretion of type I interferons and that increased interferon-I production is associated with asthma exacerbation [15,16]. Nappi et al reported a case in which two doses of the adenovirus-vectored vaccine ChAdOx1 (Astra Zeneca) progressively worsened asthma and a subsequent dose of the COVID-19 vaccine mRNA-1273 (Moderna) triggered eosinophilic granulomatosis with polyangiitis [17]. Regardless of the type of vaccine, COVID-19 vaccination itself may exacerbate asthma.…”
Section: Discussionmentioning
confidence: 99%
“…No restrictions were placed on the year of publication. Only literature published in English was selected, including studies that reported histopathological and/or cytological findings in vaccine‐related lymphadenopathy 17,20,22,23,35–64 . Studies on SLDI, which was generally detected by 18F‐FDG PET‐CT, were also selected and used for the general comprehension and description of the phenomenon and to retrieve cases evaluated by histology or LN‐FNAC 65–68 .…”
Section: Methodsmentioning
confidence: 99%
“…While most cases of SLDI do not show clinically evident enlargement of lymph nodes, an awareness of SLDI among doctors is of fundamental importance in a variety of clinical contexts, particularly with regard to cancer staging and follow‐up to avoid the risk of overdiagnosis. In our research, surgical excision or CNB of C19‐LAP‐ or SLDI‐enlarged lymph nodes have been performed in 55 cases 20,22,23,35,39,41–43,47,49–63 . The histological diagnoses were as follows: negative for neoplasia, reactive hyperplasia, and florid reactive hyperplasia (39 cases), 23,39,50–61 progressive transformation of germinal centres (1 case), 54 atypical follicular hyperplasia with light chain‐restricted germinal centres (1 case) 62 granulomatous reaction (2 cases), 50,63 metastases (4 cases), 20,22,50 Kikuchi‐Fujimoto disease (KFD; 6 cases), 40–42,49,56,64 Rosai‐Dorfman‐Destombes disease (RDD; 1 case), 48 and Langerhans cell histiocytosis (LCH; 1 case) 57 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Описано развитие тяжелого АНЦА-СВ в рамках постковидного синдрома спустя 1 мес после перенесенной SARS-CoV-2-инфекции [26]. Показано, что вакцинация против COVID-19 может осложняться формированием различных типов васкулитов, включая АНЦА-СВ [27][28][29].…”
Section: криоглобулинемический васкулит (квunclassified